The estimation of Carbon storage in Dry Evergreen and Dry Dipterocarp Forests in Sang Khom District, Nong Khai Province, Thailand - Phouveth Senpaseuth (2017)
The objectives of this study were to identify the plant community characteristics and estimate and compare the carbon storage in dry evergreen and dry dipterocarp forests, including with soil (physical and chemical) properties, in Sang Khom district, Nong Khai province. Six temporary sample plots (20×50 m2) were designed to collect data as the study area. The biomass of plant species was estimated from each of the tree components, both aboveground (stem, branch and leave) and belowground (root) portions, by using allometric equation. The biomass of the groundcover was also collected and evaporated by oven drying at 80oC for 3-5 hours or until it was at a constant weight. Then the dried weight was used to estimate the biomass content. The carbon in the biomass of the aboveground, belowground portions of the trees and the biomass of the ground cover on the soil surface were calculated by multiplying with a conversion factor at 0.5. In additions, the soil properties and soil organic carbon were analyzed. The results of this study showed that the plant community characteristic of dry evergreen and dry dipterocarp forests looked like a sparse forest, while the total carbon contents of both forest types were mostly different, especially, the aboveground carbon contents which were identified as the greatest amount of carbon contents. However, the total carbon content of dry evergreen forest was more than dry dipterocarp forest: they were 31,442.01 and 15,096.17 kg/rai, respectively. The aboveground (stem, branch and leave), belowground (root and soil) and ground cover carbon content of the dry evergreen forest was about 23,737.05, 7,682.26 and 22.71 Kg/rai, respectively. The aboveground (stem, branch and leave), belowground (root and soil) and ground cover carbon content of the dry dipterocarp forest was about 9,505.00, 5,578.57 and 12.61 kg/rai, respectively.